Knowledge and Attitude of Healthcare Workers towards the Adoption of Artificial Intelligence in Healthcare Service Delivery in Saudi Arabia - Samiyah Rafan Althaqafy, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objective: the aims of this study was to assess the knowledge and attitudes of healthcare workers towards the adoption of artificial intelligence in healthcare service delivery in Saudi Arabia. Methods: An online questionnaire was published, and responses were collected from 315 healthcare workers, including Physician, nurses, and technicians at the hospitals in Saudi Arabia. Results: Out of 320 distributed questionnaires, 315 were completed. The majority of participants demonstrated a high level of knowledge about AI and its applications in healthcare. A remarkable 76.5% agreed that AI cannot fully replace healthcare jobs. Participants also expressed concerns about the potential for AI to cause job losses. The study reveals high agreement about the potential for AI to improve patient care and provide new economic opportunities for hospitals. Statistically significant differences in perceptions of AI were found based on medical specialty and educational qualifications, but not gender, age, or years of experience. Conclusions: Healthcare workers in Saudi Arabia have a strong knowledge of AI and have mixed attitudes towards its adoption. To facilitate the integration of AI into healthcare, it is necessary to increase training and qualification of healthcare workers, and address concerns about job losses. This approach will support the advancement of healthcare services in line with the goals of Vision 2030.